2002
DOI: 10.1002/pip.411
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing technology for ribbon silicon (EFG) wafers and solar cells

Abstract: Manufacturing of wafers and solar cells based on edge-defined film-fed growth (EFG) ribbon technology has been scaled up to 20 MW in the ASE group. Highly automated manufacturing lines for wafers and solar cells have been constructed and solar cell efficiencies optimized to above the 14% level. The technology developed for these production lines incorporates new low-cost processes with minimal environmental impact and waste materials production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 4 publications
(5 reference statements)
1
12
0
Order By: Relevance
“…Record efficiencies for EFG and SR cells in the range of 18% are comparable to the best cells fabricated from multi-crystalline wafers from ingots, when lab-type processes of the same complexity are used. The same is true for industrial-type processing, with record efficiencies between 15 and 16% and mean values around 15% for EFG solar cells in production [96], slightly lower as for solar cells from ingot based wafers. From these data, it can be concluded that solar cells from EFG or SR wafers have a significant advantage concerning cost per W p , provided a comparable yield is achieved.…”
Section: Discussionsupporting
confidence: 56%
“…Record efficiencies for EFG and SR cells in the range of 18% are comparable to the best cells fabricated from multi-crystalline wafers from ingots, when lab-type processes of the same complexity are used. The same is true for industrial-type processing, with record efficiencies between 15 and 16% and mean values around 15% for EFG solar cells in production [96], slightly lower as for solar cells from ingot based wafers. From these data, it can be concluded that solar cells from EFG or SR wafers have a significant advantage concerning cost per W p , provided a comparable yield is achieved.…”
Section: Discussionsupporting
confidence: 56%
“…Large area solar cells processed according to an industrial-type fabrication scheme show significantly lower efficiencies. Record values of 15.3% for EFG material (10 × 10 cm 2 [171]) and 15.6% for SR material (8 × 10 cm 2 [172]) have been reported. One significant limitation, apart from higher shadowing losses and lower sheet resistivity, is the lack of an efficient surface texture for EFG and SR materials.…”
Section: Efg and Sr Solar Cellsmentioning
confidence: 99%
“…An interesting option in Si solar cell manufacturing is the growth of ribbons [62,63]. Ribbons do not require the expensive sawing process.…”
Section: Crystalline Silicon Progress and Challengesmentioning
confidence: 99%